2019
DOI: 10.1016/j.envpol.2018.11.059
|View full text |Cite
|
Sign up to set email alerts
|

Sources and dry deposition of carbonaceous aerosols over the coastal East China Sea: Implications for anthropogenic pollutant pathways and deposition

Abstract: While many studies have been conducted on carbonaceous aerosols in urban areas worldwide, investigations of carbonaceous components in marine atmospheres are rather limited. In this study, 75 paired total suspended particle (TSP) and PM2.5 samples were collected over four seasons on Huaniao Island (HNI), an island that lies downwind of continental pollutants emitted from mainland China moving towards the East China Sea (ECS). These samples were analyzed for organic carbon (OC) and elemental carbon (EC), with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Half of the low-temperature combustion-generated ECs were Char-EC. This finding is concordant with previous research results. ,, It can be seen in Figure S3 that the R S/C varied markedly from 0.15 to 23.8 in particle samples from different sources or from different ambient samples. Generally, the fuel types can significantly affect the value of R S/C in carbonaceous particles; vapor-phase carbon black has the highest value of R S/C followed by diesel vehicle emission and residential coal combustion has the lowest value of R S/C . However, the value of R S/C from the same fuel types still can be different due to the difference in the operation method (e.g., R S/C of diesel soot higher than that from diesel vehicle emission for 1 order of magnitude).…”
Section: Resultssupporting
confidence: 90%
“…Half of the low-temperature combustion-generated ECs were Char-EC. This finding is concordant with previous research results. ,, It can be seen in Figure S3 that the R S/C varied markedly from 0.15 to 23.8 in particle samples from different sources or from different ambient samples. Generally, the fuel types can significantly affect the value of R S/C in carbonaceous particles; vapor-phase carbon black has the highest value of R S/C followed by diesel vehicle emission and residential coal combustion has the lowest value of R S/C . However, the value of R S/C from the same fuel types still can be different due to the difference in the operation method (e.g., R S/C of diesel soot higher than that from diesel vehicle emission for 1 order of magnitude).…”
Section: Resultssupporting
confidence: 90%
“…5b)), probably due to the input from atmospheric deposition during winter, and the relatively low CDOM concentrations in bulk water. Atmospheric deposition of organic carbon and nutrients were found a peak in winter over the coastal ECS (Wang et al, 2019). We suggested that the EFs of CDOM The SML is an aggregate-enriched biofilm environment with distinct microbial communities,…”
Section: Photochemical Degradation Of Dom In the Ssw And The Smlmentioning
confidence: 84%
“…When the OC/EC ratios exceed 2.0, the relationship of OC and EC can be used to estimate the SOC as (Turpin et al, 1995 (Chow et al, 1996;Castro et al, 1999;Cao et al, 2005;Feng et al, 2009). However, the ratio of char to soot (char/soot) may also be a valuable indicator to imply source variations since there are distinct changes between different emission sources (Han et al, 2010;Wang et al, 2019). for SOC and 33.0% for SOC/EC, respectively.…”
Section: Soc Estimation and Sources From Oc/ec And Char/soot Ratiosmentioning
confidence: 99%